1999
DOI: 10.1183/09031936.99.13614119
|View full text |Cite
|
Sign up to set email alerts
|

Sampling of exhaled nitric oxide in children: end-expiratory plateau, balloon and tidal breathing methods compared

Abstract: Personally measured weekly exposure to NO 2 and respiratory health among preschool children. K. Mukala, J. Pekkanen, P. Tiittanen, S. Alm, R.O. Salonen, J. Tuomisto. #ERS Journal Ltd 1999. ABSTRACT: Nitrogen dioxide is known as a deep lung irritant. The aim of this study was to find out whether the relatively low ambient air NO 2 concentrations in the northern city of Helsinki had an impact on the respiratory health of children.The association between personal exposure to ambient air NO 2 and respiratory healt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
48
1
1

Year Published

2001
2001
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 35 publications
(20 reference statements)
3
48
1
1
Order By: Relevance
“…Correlations of different on-and off-line sampling techniques have been reported in the literature [7,[11][12][13][14]. Several authors found an excellent correlation between on-and off-line values; however, agreement between both methods differed in different studies.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Correlations of different on-and off-line sampling techniques have been reported in the literature [7,[11][12][13][14]. Several authors found an excellent correlation between on-and off-line values; however, agreement between both methods differed in different studies.…”
Section: Discussionmentioning
confidence: 95%
“…On the other hand, exhalation flow cannot easily be controlled and it is difficult to prevent nasal contamination adequately, leading to increased variation in FENO values. Uncontrolled single exhalations against a resistance are easy to perform and reproducible even in young children, and there is no need for expensive or complicated equipment [7,14,16]. However, in the absence of flow control, FENO values may vary and be unsuitable to monitor individual patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For this reason, simpler but less standardized techniques have been introduced in an attempt to overcome the poor compliance of children, including tidal-breath eNO measurements (eNO TB ) with or without flow control, and offline reservoir sampling (1,(11)(12)(13). Unfortunately, these do not provide accurate data because they have some methodological drawbacks, such as the use of uncontrolled expiratory flow and nasal NO contamination (1).…”
mentioning
confidence: 99%